The Significance of Neutrophil Extracellular Traps in Colorectal Cancer and Beyond: From Bench to Bedside - Li, Dingchang; Shao, Jiakang; Cao, Bo; Zhao, Ruiyang; Li, Hanghang; Gao, Wenxing; Chen, Peng; Jin, Lujia; Cao, Li; Ji, Shuaifei; Dong, Guanglong (Frontiers in Oncology, 2022)
Neutrophil extracellular traps (NETs), products of neutrophil death when exposed to certain stimuli, were first proposed as a type of response to bacterial infection in infectious diseases. Since then, extensive studies have discovered its involvement in other non-infectious inflammatory diseases including thromboembolism, autoimmune diseases, and cancer. Colorectal cancer (CRC) is one of the most common malignancies in the world. NET formation is closely associated with tumorigenesis, progression, and metastasis in CRC. Therefore, the application of NETs in clinical practice as diagnostic biomarkers, therapeutic targets, and prognostic predictors has a promising prospect. In addition, therapeutics targeting NETs are significantly efficient in halting tumor progression in preclinical cancer models, which further indicates its potential clinical utility in cancer treatment. This review focuses on the stimuli of NETosis, its pro-tumorigenic activity, and prospective clinical utility primarily in but not limited to CRC.